SATISFACTION OF CAREGIVERS OF Serious Mental illness (SMI) PATIENTS AT REHABILITATION SERVICE CENTRE - Saxena, Osheen; Kiran Singh, Thiyam; Kaur, Navneet (International Journal of Psychosocial Rehabilitation, 2024)
Psychiatric rehabilitation services have a goal of catering to the rehabilitative needs of patients such as their psychiatric symptoms, cognitive needs, emotional needs, social needs, vocational training needs and placement. The satisfaction of caregivers of patients with the rehabilitation services is an important marker of the success of any rehabilitation facility.To assess the satisfaction of caregivers of serious mental illness (SMI) patients at Disability Assessment & Rehabilitation Triage (DART), Chandigarh, with the services provided.The assessment of satisfaction was done using a semi structured interview based on a questionnaire adapted from the “Patient Satisfaction Questionnaire” by the Wirral Community, NHS Trust, UK. The sample consisted of 25 caregivers of patients seeking treatment from DART. Descriptive statistics was used to analyse the data.The results indicated that 84% of caregivers feel involved in and informed about treatment decisions regarding treatment of the patient. 74% of caregivers feel that they have been better able to understand the patient’s illness after coming to DART. 96% caregivers believe in the competency of the professionals. 92% believe that patient information is kept confidential. 76% agree there is improvement in the mental health of patients post rehabilitative care. 68% report improvement in the functional living skills of patients and 80% report improvement in QOL of both patients and family members. The individual feedback & suggestions involved, adding more no. of activities, taking measures to avoid patient neglect, more attention to caregivers and improvement in placement services.The study reveals that majority of caregivers interviewed are satisfied with rehabilitative care of patients at DART, GMCH, Chandigarh. However, feedback included useful suggestions for improvement in the areas of patient care, caregiver support and placement.